The Relationship between Mental Toughness and Anxiety in Athletes: A Meta-Analysis Study - Islam, Syahrizal; Husein, Muhamad; Hasan, Baharuddin; Muti, Gilang Gemilang; Muti, Nabella Salsabila; Lembang, Melyani Taruk; Nubatonis, Jefrio Demitrimus; Kristiono, Aljawahir Agus; Taiar, Redha; Salacup, Vince Louisse D. (Universitas Negeri Surabaya, 2025)
Purpose: This study was motivated by the importance of the role of psychological aspects, especially mental toughness, in supporting athletes' abilities when facing anxiety in a match. Materials and Methods: This study used a meta-analysis method. The search used the Publish and Publish application, with Google Scholar as the database. Literature searches from various sources used the keywords: